Intensive Cardiac Rehabilitation Is Markedly Underutilized by Medicare Beneficiaries: RESULTS FROM A 2012-2016 NATIONAL SAMPLE. Issue 3 (9th September 2021) - Husaini, Mustafa; Deych, Elena; Racette, Susan B.; Rich, Michael W.; Joynt Maddox, Karen E.; Peterson, Linda R.
Abstract : Intensive cardiac rehabilitation (ICR) has been Medicare-approved since 2010, yet little is known about national utilization rates of ICR in the Medicare population or characteristics associated with its use. In a longitudinal Medicare 5% sample from 2012 to 2015, ICR is not widely available and remains markedly underutilized. Abstract : Purpose: Intensive cardiac rehabilitation (ICR) was developed to enhance traditional cardiac rehabilitation (CR) by adding sessions focused on nutrition, lifestyle behaviors, and stress management. Intensive CR has been Medicare-approved since 2010, yet little is known about national utilization rates of ICR in the Medicare population or characteristics associated with its use. Methods: A 5% sample of Medicare claims data from 2012 to 2016 was used to identify beneficiaries with a qualifying indication for ICR/CR and to quantify utilization of ICR or CR within 1 yr of the qualifying diagnosis. Results: From 2012 to 2015, there were 107 246 patients with a qualifying indication. Overall, only 0.1% of qualifying patients participated in ICR and 16.2% in CR from 2012 to 2016, though utilization rates of both ICR and CR increased during this period (ICR 0.06 to 0.17%, CR 14.3 to 18.2%). The number of ICR centers increased from 15 to 50 over the same period. There were no differences between ICR and CR enrollees with respect to age, sex, race, discharge location, median income, dual enrollment, or number of comorbidities. Compared with eligible beneficiaries who did not attend ICR or CR, those who attended either program were younger, more likely to be male and White, and had higher median income. Conclusions: Although ICR and CR have a class 1 indication for the treatment of cardiovascular disease and the number of ICR centers has increased, ICR is not widely available and remains markedly underutilized. Continued research is needed to understand the barriers to program development and patient participation.